Asthma routinization, family asthma management, caregiver depressive symptoms, and medication adherence in Head Start preschool children - Lu, Monica A.; Ruvalcaba, Elizabeth; McQuaid, Elizabeth L.; Rand, Cynthia S.; Riekert, Kristin A.; Eakin, Michelle N. (Frontiers in Allergy, 2023)
Medication adherence is suboptimal in childhood asthma. Children rely on caregivers to manage medication administration. It is important to detect families who are at risk for poor adherence or to identify potential areas that can assist families with better adherence to asthma medications in order to improve asthma outcomes. We investigated the association between asthma routines, family asthma management knowledge and skills, and caregiver depressive symptoms with daily controller medication adherence among Head Start preschool children in Baltimore City. Our study included 256 low-income urban preschool children who were prescribed a daily controller medication. Asthma routinization (by the Asthma Routines Questionnaire), family asthma management (by the Family Asthma Management System Scale (FAMSS)), and caregiver depressive symptoms (by the Center for Epidemiological Studies -Depression) were assessed at baseline. The medication possession ratio (MPR) to measure adherence to daily controller medications was calculated at baseline and 12 months from pharmacy fill records. Multiple regression models evaluated the relationship between asthma routinization, the FAMSS, the CES-D, and MPR. Results indicated that only 7% of families had an MPR above 80% at baseline, and 24% of caregivers had clinically significant depressive symptoms. Higher asthma medication routines were associated with higher MPR at baseline (b=0.05, p=0.03). Higher family asthma management was associated with higher MPR at both baseline (b=0.04, p<0.01) and 12 months (b=0.05, p<0.01). Our findings highlight the importance of family asthma management and maintaining medication routines over time to improve asthma controller medication adherence.